2023
DOI: 10.1021/acsomega.3c00159
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Effect of Phospholipid Charge on the Rate of Insulin Aggregation and Structure and Toxicity of Amyloid Fibrils

Abstract: The plasma membrane is a dynamic structure that separates the cell interior from the extracellular space. The fluidity and plasticity of the membrane determines a large number of physiologically important processes ranging from cell division to signal transduction. In turn, membrane fluidity is determined by phospholipids that possess different charges, lengths, and saturation states of fatty acids. A growing body of evidence suggests that phospholipids may play an important role in the aggregation of misfolde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Recently reported results by Zhaliazka and co-workers showed that such lipid-determined toxicity of oligomers and fibrils could be a general phenomenon typical for a large group of amyloidogenic proteins. , Specifically, the researchers showed that the secondary structure and toxicity of amyloid β 1–42 (Aβ 1–42 ) oligomers and fibrils could be uniquely altered by cholesterol (Cho), cardiolipin (CL), and PC . Similar results were also reported by Matveyenka and co-workers for insulin and lysozyme. …”
Section: Introductionsupporting
confidence: 55%
“…Recently reported results by Zhaliazka and co-workers showed that such lipid-determined toxicity of oligomers and fibrils could be a general phenomenon typical for a large group of amyloidogenic proteins. , Specifically, the researchers showed that the secondary structure and toxicity of amyloid β 1–42 (Aβ 1–42 ) oligomers and fibrils could be uniquely altered by cholesterol (Cho), cardiolipin (CL), and PC . Similar results were also reported by Matveyenka and co-workers for insulin and lysozyme. …”
Section: Introductionsupporting
confidence: 55%
“…Experimental results reported by our group and other research groups demonstrated that lipids uniquely altered the morphology and secondary structure of amyloid aggregates formed in their presence. ,, ,, Specifically, both insulin and lysozyme formed spherical oligomers in the presence of PC and PE. , These aggregates dominated by unordered protein secondary structure possessing very few if any β-sheets. At the same time, insulin and lysozyme formed fibrils in the presence of negatively charged lipids, such as CL, PS, and PG. , These aggregates were dominated by a parallel β-sheet secondary structure.…”
Section: Structural Organization Of Amyloid Oligomers and Fibrilsmentioning
confidence: 68%
“…There are also numerous pieces of experimental evidence indicating that lipids change the secondary structure and morphology of amyloid oligomers and fibrils formed in their presence. Such fibrils exert drastically different levels of cell toxicity compared to amyloid oligomers and fibrils formed in the lipid-free environments. ,,,, …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations